The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/mnfr.201400614
|View full text |Cite
|
Sign up to set email alerts
|

Citrus nobiletin ameliorates experimental colitis by reducing inflammation and restoring impaired intestinal barrier function

Abstract: Nobiletin exerted anti-inflammatory effects in TNBS-induced colitis through the downregulation of inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX-2) expression. Nobiletin restored barrier function, which had been damaged after TNBS administration, through the inhibition of the Akt-NF-κB-MLCK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 57 publications
5
57
0
Order By: Relevance
“…In the present study, we demonstrated that nobiletin prevents the proliferation and migration of glioma cells by inhibiting MAPK and Akt pathways. Recently, nobiletin has attracted a considerable amount of interest because of its multiple biological activities, particularly anti-inflammatory and anticarcinogenic activities (Chien et al, 2015;Guo et al, 2012;Morley et al, 2007;Xiong et al, 2015). Nobiletin has been reported to exhibit an antiproliferative effect and anti-invasive activity against various cancer cells (Chien et al, 2015; Miyamoto et al, 2008;Morley et al, 2007;Shi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that nobiletin prevents the proliferation and migration of glioma cells by inhibiting MAPK and Akt pathways. Recently, nobiletin has attracted a considerable amount of interest because of its multiple biological activities, particularly anti-inflammatory and anticarcinogenic activities (Chien et al, 2015;Guo et al, 2012;Morley et al, 2007;Xiong et al, 2015). Nobiletin has been reported to exhibit an antiproliferative effect and anti-invasive activity against various cancer cells (Chien et al, 2015; Miyamoto et al, 2008;Morley et al, 2007;Shi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It can been extracted from different citrus species, such as Citrus reticulata Blanco (mandarin orange), Citrus unshiu Markovich, Citrus depressa (shiikuwasa) and Citrus limon (lemon) (24). Nobiletin has been reported to be an encouraging antioxidant and anti-inflammatory agent in the treatment of asthma, colitis and Alzheimer's disease (2,5,6). Nobiletin has been reported to protect PC12 cells from hydrogen peroxide (H 2 O 2 )-induced cytotoxicity (7), and to atttenuate ethanol-induced liver injury by augmenting the phosphorylation of AMP-activated protein kinase (AMPK) (8).…”
Section: Introductionmentioning
confidence: 99%
“…The signalling pathways that nobiletin may interact with were explored in placenta, VAT and skeletal muscle stimulated with TNF ( Figure 4). Nobiletin has been shown to regulate numerous signalling pathways including NF-κB in murine macrophages [42], Akt in intestinal Caco-2 cells [43] and MAPK pathways in human fibroblasts [44]. Therefore, it was of interest to determine if nobiletin also targets these signalling pathways in the present study.…”
Section: Nobiletin Acts Through Nf-κb Akt and Mapk Erk Pathways In Pmentioning
confidence: 97%